TO THE PROBLEM OF INTRODUCTION OF GIS-TECHNOLOGIES IN MAINTENANCE OF STABILITY OF NATURAL SYSTEMS (Journal of Geography and Environmental Management, 2016)
In article are resulted an example of use of GIS-technology in geoecology sphere on an example of the componental analysis. Also questions of an estimation of influence of the concrete ecological factor on a condition of natural system and to construction of an estimated scale for mapping of a spatial variation of results of a complex estimation are considered.